2019
DOI: 10.1016/j.neuropsychologia.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

What bilateral damage of the superior parietal lobes tells us about visual attention disorders in developmental dyslexia

Abstract: Neuroimaging studies have identified the superior parietal lobules bilaterally as the neural substrates of reduced visual attention (VA) span in developmental dyslexia. It remains however unclear whether the VA span deficit and the deficits in temporal and spatial attention shifting also reported in dyslexic children reflect a unitary spatio-temporal deficit of attention - probably linked to general posterior parietal dysfunction- or the dysfunction of distinct attentional systems that relate to different neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 88 publications
(125 reference statements)
5
38
1
1
Order By: Relevance
“…It can be very similarly estimated using nonverbal tasks and non-verbal stimuli, like symbols or pseudo-letters (Chan & Yeung, 2020;Lobier et al, 2012). Performance on VA span tasks reflects the amount of visual attention capacity available for processing (Dubois et al, 2010;Lobier et al, 2013), which relates to the dorsal attention network (Lobier et al, 2014(Lobier et al, , 2012Reilhac et al, 2013;Valdois et al, 2019aValdois et al, , 2014. Individuals with higher VA span show more efficient word recognition skills, thus faster reading (Antzaka et al, 2017;Bosse & Valdois, 2009;Lobier et al, 2013;Valdois et al, 2019b), more accurate irregular word reading (Bosse & Valdois, 2009) and smaller length effects (van den Boer et al, 2013); for computational modelling, see Ginestet et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…It can be very similarly estimated using nonverbal tasks and non-verbal stimuli, like symbols or pseudo-letters (Chan & Yeung, 2020;Lobier et al, 2012). Performance on VA span tasks reflects the amount of visual attention capacity available for processing (Dubois et al, 2010;Lobier et al, 2013), which relates to the dorsal attention network (Lobier et al, 2014(Lobier et al, , 2012Reilhac et al, 2013;Valdois et al, 2019aValdois et al, , 2014. Individuals with higher VA span show more efficient word recognition skills, thus faster reading (Antzaka et al, 2017;Bosse & Valdois, 2009;Lobier et al, 2013;Valdois et al, 2019b), more accurate irregular word reading (Bosse & Valdois, 2009) and smaller length effects (van den Boer et al, 2013); for computational modelling, see Ginestet et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…They thus appear as potential underpinnings of the phonological deficit rather than independent sources of poor reading outcome. In contrast, another type of visual attention mechanism, the visual attention span (VAS)—that dissociates from visual attention orientation and visual attention shifting (Lallier et al, 2010; Valdois et al, 2019b) and is reported in dyslexic individuals who have good PA (Bosse et al, 2007)—affects reading performance independent of phonological skills in both developmental dyslexia (Bosse et al, 2007; Saksida et al, 2016; Zhao et al, 2018) and typical reading (Bosse & Valdois, 2009; Van den Boer et al, 2013, 2015). In support of two PA and VAS reading-related independent skills, a neural dissociation was found to mirror the cognitive dissociation between PA and VAS deficits in developmental dyslexia (Peyrin et al, 2012).…”
mentioning
confidence: 99%
“…However, performance on the JLAP was just as important in predicting oral reading accuracy as mathematics achievement, indicating that visuospatial attention is not uniquely related to mathematics learning. Indeed, prior studies have found that deficits in visuospatial attention contribute to reading difficulties, including word reading errors (Friedrich et al, 1985;Valdois et al, 2019). Valdois et al's (2019) study suggests that the deficits are associated with the top-down control of visual attention.…”
Section: Individual Differences In Achievementmentioning
confidence: 87%
“…Indeed, prior studies have found that deficits in visuospatial attention contribute to reading difficulties, including word reading errors (Friedrich et al, 1985;Valdois et al, 2019). Valdois et al's (2019) study suggests that the deficits are associated with the top-down control of visual attention. Deficits in control of visual attention would hamper the processing of visually and sequentially presented details, which would make accurate reading and many aspects of mathematics (e.g., processing an equation) error prone.…”
Section: Individual Differences In Achievementmentioning
confidence: 87%